2012
DOI: 10.1155/2012/595821
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Heart Failure

Abstract: Cognitive impairment (CI) is increasingly recognized as a common adverse consequence of heart failure (HF). Although the exact mechanisms remain unclear, microembolism, chronic or intermittent cerebral hypoperfusion, and/or impaired cerebral vessel reactivity that lead to cerebral hypoxia and ischemic brain damage seem to underlie the development of CI in HF. Cognitive decline in HF is characterized by deficits in one or more cognition domains, including attention, memory, executive function, and psychomotor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 95 publications
2
86
2
2
Order By: Relevance
“…The link between multimorbidity and cognitive function is plausible, given the interrelatedness between physical and cognitive functioning (Wang et al 2006), as physiological-related chronic diseases include several pathological processes (e.g., amyloid aggregation, vascular damage) interlinked with cognitive dysfunction. Each of the individual chronic diseases included in the multimorbidity index has been previously shown to associate with cognitive dysfunction, including arthritis (Shin et al 2012), cardiovascular disease (Dardiotis et al 2012;Waldstein and Wendell 2010), hypertension (Novak and Hajjar 2010), diabetes (Arvanitakis et al 2006), cancer (Biegler et al 2009), and obesity (Smith et al 2011). The possibility of physical activity potentially moderating the multimorbidity-cognitive function relationship is plausible given the established and growing body of research demonstrating physical activityinduced beneficial effects on preserving cognitive function (Loprinzi 2015c;Loprinzi et al 2013bLoprinzi et al , 2015 as well as helping prevent and treat multimorbidity (Dankel et al 2015;Loprinzi 2015c).…”
Section: Discussionmentioning
confidence: 99%
“…The link between multimorbidity and cognitive function is plausible, given the interrelatedness between physical and cognitive functioning (Wang et al 2006), as physiological-related chronic diseases include several pathological processes (e.g., amyloid aggregation, vascular damage) interlinked with cognitive dysfunction. Each of the individual chronic diseases included in the multimorbidity index has been previously shown to associate with cognitive dysfunction, including arthritis (Shin et al 2012), cardiovascular disease (Dardiotis et al 2012;Waldstein and Wendell 2010), hypertension (Novak and Hajjar 2010), diabetes (Arvanitakis et al 2006), cancer (Biegler et al 2009), and obesity (Smith et al 2011). The possibility of physical activity potentially moderating the multimorbidity-cognitive function relationship is plausible given the established and growing body of research demonstrating physical activityinduced beneficial effects on preserving cognitive function (Loprinzi 2015c;Loprinzi et al 2013bLoprinzi et al , 2015 as well as helping prevent and treat multimorbidity (Dankel et al 2015;Loprinzi 2015c).…”
Section: Discussionmentioning
confidence: 99%
“…29 While it is thought that altered cognitive function in heart failure is due to impaired cerebral perfusion and oxygenation, our results suggest that deficits may also be associated with the effects of hypertension, age, stroke, and statin use. [4][5][6]30 At this time the precise etiology of CI in our population of advanced heart failure patients is not clear. It has been reported that impaired cognitive function in patients with heart failure improves significantly following cardiac transplantation and pacemaker implantation in bradycardic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…3 Cognitive impairment (CI) is frequent in HF patients, with prevalence ranging from 25% to 75%, and is thought to be related to poor cerebral perfusion resulting from low cardiac output, low systolic blood pressure, and impaired cerebral neurohormonal autoregulation in HF. [4][5][6][7] Decreased neurocognitive function can lead to adverse clinical outcomes, poor quality of life, increased readmissions, high cost of care, and increased mortality following surgical intervention for advanced HF. 8 Individuals with mild cognitive impairment (MCI) are at increased risk of progression to dementia.…”
mentioning
confidence: 99%
“…In NYHA class III-IV patients, cerebral blood flow was reduced by 30%, when captured by single-photon emission computed tomography. Moreover, low systolic blood pressure has been described as an independent predictor of cognitive impairment in heart failure patients [28]. As mean arterial pressure decreases beyond 80% of baseline or 60 mm Hg, cerebral blood flow declines [29].…”
Section: Role Of Imagingmentioning
confidence: 99%